Diskursus Ekoteology Islam dalam Pengalaman Perlindungan Hutan Mangrove Bersama Komunitas Muslim di Seram Timur-Maluku - Saidin Ernas; Baco Sarluf; Muhammad Ipaloat (MANGENTE: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
This paper is a development of a report on community service activities carried out with the Muslim community in the village of Geser Seram Timur-Maluku. Through the approach of "Islamic Ecotheology," this paper wants to describe three things. First, the idea of an eco-theological vision in the coastal Muslim community is a contextual need that needs to be continuously emphasised to build awareness in the Muslim community that protecting and caring for the natural environment is part of a Muslim's theological duties. Second, through various forms of activities such as lectures, discussions, and film screenings about environmental damage and conservation efforts that can be carried out independently, the assisted subjects can participate in caring for the natural environment in their places. Third, eco-awareness will encourage sustainable initiatives in Muslim society as human beings who have been shown by the assisted subjects in the village to restore the natural environment as part of religious teachings, especially to protect mangrove forests, which have various functions for the balance of the ecosystem.Keywords: Islamic ecotheology, Muslim society, mangroves, East Seram-Maluku